2017
DOI: 10.1093/femsre/fux044
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the bulk: disclosing the life of single microbial cells

Abstract: Microbial single cell analysis has led to discoveries that are beyond what can be resolved with population-based studies. It provides a pristine view of the mechanisms that organize cellular physiology, unbiased by population heterogeneity or uncontrollable environmental impacts. A holistic description of cellular functions at the single cell level requires analytical concepts beyond the miniaturization of existing technologies, defined but uncontrolled by the biological system itself. This review provides an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 327 publications
(504 reference statements)
0
31
0
1
Order By: Relevance
“…The heterogeneity among budding cells was reduced during the growth phase, while it was higher in the lag phase. As recent studies have shown, bet-hedging mechanisms may be the reason for prolonged growth delay periods due to the formation of subpopulations with different phenotypes when cells cope with environmental stress, as it occurs after inoculation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity among budding cells was reduced during the growth phase, while it was higher in the lag phase. As recent studies have shown, bet-hedging mechanisms may be the reason for prolonged growth delay periods due to the formation of subpopulations with different phenotypes when cells cope with environmental stress, as it occurs after inoculation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The value of single-cell analysis has long been appreciated for different biological systems, ranging from microorganisms [ 48 ] to human cells [ 49 , 50 , 51 , 52 ]. There have been excellent reviews on the clinical implications of tumor heterogeneity and methodologies for its study at the single cell level (e.g., [ 50 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidic parallelization and single-cell monitoring allows the measurement and averaging of parameters on hundreds of individual cells, compared to measuring parameters of a whole cell population. New insights can be obtained by observing single cells, such as the monitoring of certain classes of proteins, using fluorescently tagged proteins [102,103] and give information about the cell-to-cell variation in a heterogeneous microbial population [104][105][106]. Automation of microfluidic cell culture systems also leads to standardized manipulation and monitoring, which allows the perfect timing of protocols to characterize dynamic processes at high temporal resolution to be performed [94].…”
Section: Microfluidic High-throughput Antifungal Drug Discoverymentioning
confidence: 99%